Jorge Amado, cacau... e o que mais ilhéus tem?: um estudo das dimensões da imagem do destino turístico - Lílian Dominguez Santana (2016)
This study analyzes the formation of tourist destination image and its influence on behavioral intentions to return and recommendation from the proposition and validation of a theoretical model that examined: the relationship between four destination image dimensions (cognitive, affective, single, global); the influence of familiarity (informative and experiential), the sociodemographic characteristics and tourist motivations on these dimensions and the influence of global image on behavioral intentions. The empirical test of the model was carried out with reference to the unit Ilheus / BA destination. Initially, qualitative survey was conducted to survey unique attributes of fate, aiming at building a single image scale and later quantitative survey was conducted from online and face survey, yielding a total of 396 valid questionnaires for visitors and 70 valid questionnaires for residents. A survey of residents was carried out to obtain comparative reference in the descriptive analysis of the data regarding the destination image Ilheus, since the image of residents is considered more precise; However, to validate the model was considered the only visitors. The analysis of qualitative data was given from the content analysis method. The quantitative data analysis was made from the exploratory factor analysis, to reduce factors, and structural equation modeling, to validate the hypothetical model proposed. The main results relate to the relationship between the target image dimensions, with the overall image being affected by the affective image (feelings), and the only image being substantially influenced by cognitive image (knowledge). The direct relationship between the uniqueness of perceptions (single image) on the overall picture was not significant, but was found to mediate the emotional image that relationship. The information familiarity and motivations influence mainly, and positively, cognitive image; already, experiential familiarity exerts negative influence on cognitive and positive image on single image, indicating that the higher the degree of contact with the target, the greater the perception of uniqueness, however, are more critical evaluations. Among the socio-demographic characteristics, education and income / social class are the most significant and negatively affect cognitive image. Finally, the influence of the overall image on behavioral intent was also confirmed.